Captain America : man out of time, Part 4 - Waid, Mark, 1962- (Spotlight, 2012)
Frozen in suspended animation for over sixty years, World War II superhero Captain America, aka Steve Rogers, wakes up in the twenty-first century and must adapt to a very changed world.